1992
DOI: 10.3758/bf03330463
|View full text |Cite
|
Sign up to set email alerts
|

Recall of congruent information in the self-reference task

Abstract: Information descriptive of the self has prior associations with the representation of the self in memory . Therefore, information descriptive of the self should be recalled better than information not descriptive of the self. This is the congruent-information hypothesis. A related hypothesis, the trait-superiority hypothesis, states that trait adjectives are more easily recalled using a self-reference task than using another task. The results of previous research are equivocal with regard to the congruent-info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…According to the self-consistency theory, individuals process social information in a self-consistent direction to protect themselves from disruptive changes in the organization of the self-concept. That is, social information that is congruent with one's self-concept may receive more attention and may be remembered better than incongruent information (Bellezza, 1992;Best, Stapleton, & Downey, 2005). Similarly, Swann, Stein-Seroussi, and Giesler (1992) suggested that individuals tend to verify their self-concepts by approaching situations that can provide feedback to fit their self-concept.…”
Section: Subordinate's Core Self-evaluationsmentioning
confidence: 99%
“…According to the self-consistency theory, individuals process social information in a self-consistent direction to protect themselves from disruptive changes in the organization of the self-concept. That is, social information that is congruent with one's self-concept may receive more attention and may be remembered better than incongruent information (Bellezza, 1992;Best, Stapleton, & Downey, 2005). Similarly, Swann, Stein-Seroussi, and Giesler (1992) suggested that individuals tend to verify their self-concepts by approaching situations that can provide feedback to fit their self-concept.…”
Section: Subordinate's Core Self-evaluationsmentioning
confidence: 99%
“…Indeed, one may need to reference one’s self knowledge in order to incorporate the thoughts, feelings, and sensory experiences that one might have when present at the imagined event. Numerous studies have demonstrated that processing information in reference to oneself is an exceptional strategy for enhancing memory (Bellezza, 1992; Klein, Loftus, & Burton, 1989; Maki & McCaul, 1985; Rogers, Kuiper, & Kirker, 1977). In fact, self-referential strategies have been found to enhance memory to a greater degree than other successful encoding strategies – a phenomenon often referred to as the “self-reference effect” (for a review, see Symons & Johnson, 1997) – and initial findings suggest that individuals with compromised memory functioning demonstrate benefits from self-referential processing as well.…”
mentioning
confidence: 99%
“…The form of distortion is often in its own image. That is, the self-system functions conservatively, often biasing the processing of selfrelevant information in a self-consistent direction (Bellezza, 1992). One functional aspect of this conservatism is its potential for guarding against disruptive changes in the organization of the self-concept, especially those precipitated by discrepant information (Epstein, 1973;Swann, 1987Swann, , 1990.…”
Section: Self-consistent Selectivitymentioning
confidence: 99%